An estimation of the production function of fisheries in Peam Krasaob Wildlife Sanctuary in Koh Kong Province, Cambodia - Kong Sopheak; Cheb Hoeurn (Los Baños, Laguna, Philippines WorldFish (ICLARM)-Economy and Environment Program for Southeast Asia (EEPSEA), 2016)
This report presents an economic analysis of the different uses and the indirect use value of mangroves in terms of their support as nurseries and breeding grounds for commercially important finfish in Koh Kong, Kep, Kampot, and Preah Sihanouk, which are four coastal provinces in Cambodia. A total of 300 households in four different locations that have different mangrove characteristics were surveyed in order to collect information on the traditional uses of mangrove extracted by the local communities. This study estimated the direct use value of mangrove products collected by households, including fuelwood, charcoal, wood for construction materials, fish, and snails. It also estimated the indirect use value of mangrove forest resulting from its nursery and breeding ground services for commercially important finfish. The results of the study showed that both the direct and indirect values derived from mangrove forests are very high. Thus, failing to find and implement appropriate management strategies and policies on mangroves conservation would lead not only to serious or irreversible ecological degradation, but also to substantial economic losses.
"February, 2016"--Title page.
Includes bibliographical references (pages 27-28)
Keywords: Mangrove fisheries -- Cambodia -- Peam Krasaob Wildlife Sanctuary; Mangrove fisheries -- Economic aspects -- Cambodia; Fisheries -- Economic aspects -- Cambodia